2020
DOI: 10.1002/jbmr.4181
|View full text |Cite
|
Sign up to set email alerts
|

Health Service Use and Quality of Life Recovery 12 Months Following Major Osteoporotic Fracture: Latent Class Analyses of the International Costs and Utilities Related to Osteoporotic Fractures Study (ICUROS)

Abstract: Major osteoporotic fractures (MOFs) are associated with a rapid decline in health‐related quality of life (HRQoL); however, there is limited knowledge about which healthcare services positively affect HRQoL postfracture. This study aimed to identify specific combinations of health service use associated with recovery of HRQoL 12 months post‐MOF. The analyses included 4126 adults aged ≥50 years with an MOF (1657 hip, 1354 distal forearm, 681 vertebrae, 434 humerus) participating in the International Costs and U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…A recent systematic review51 identified that health literacy interventions in low-income and middle-income countries were primarily functional in nature, i.e., focused on improving knowledge and understanding at the individual level—there was less emphasis on the role of health services and systems in addressing health literacy barriers. Further research in low-income and middle-income countries is required that incorporates individual and system-level factors; however, it is important that this is locally driven with an understanding of contextual factors 52…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review51 identified that health literacy interventions in low-income and middle-income countries were primarily functional in nature, i.e., focused on improving knowledge and understanding at the individual level—there was less emphasis on the role of health services and systems in addressing health literacy barriers. Further research in low-income and middle-income countries is required that incorporates individual and system-level factors; however, it is important that this is locally driven with an understanding of contextual factors 52…”
Section: Discussionmentioning
confidence: 99%
“…Further research in low-income and middle-income countries is required that incorporates individual and system-level factors; however, it is important that this is locally driven with an understanding of contextual factors. 52…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…HRQoL will be assessed via survey at baseline, and at 6 and 12 months using the validated EuroQoL questionnaire (EQ-5D-5L) 35. The EQ-5D-5L utility index scores will be calculated using Australian time utility weights from general Australian population samples 36…”
Section: Methods and Analysismentioning
confidence: 99%
“…Osteoporosis is a systemic bone disease that is characterized by a decrease in bone mass, a deterioration of the microstructure of bone tissue, and a decrease in bone strength, leading to an increase in bone fragility and susceptibility to fractures (1). Clinical vertebral and femoral neck fractures are severe osteoporotic fractures that result in increased disability, morbidity, and mortality (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) higher healthcare costs (11)(12)(13)(14)(15), and affect health-related quality of life (16)(17)(18)(19)(20)(21). Although studies have shown a very low incidence of osteoporotic fractures in the Chinese mainland population (22), the incidence of osteoporotic fractures is increasing rapidly with the urbanization and aging of the Chinese population (23).…”
Section: Introductionmentioning
confidence: 99%